2020
DOI: 10.1111/pcn.13020
|View full text |Cite
|
Sign up to set email alerts
|

Low dopamine transporter binding in the nucleus accumbens in geriatric patients with severe depression

Abstract: AimDysfunction of dopaminergic neurons in the central nervous system is considered to be related to major depressive disorder (MDD). Especially, MDD in geriatric patients is characterized by anhedonia, which is assumed to be associated with reduced dopamine neurotransmission in the reward system. Dopamine transporter (DAT) is considered to reflect the function of the dopamine nerve system. However, previous DAT imaging studies using single photon emission computed tomography or positron emission tomography (PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Studies of D2/D3 receptor binding using PET in young or midlife populations are mixed, with some finding increased receptor availability in MDD, potentially reflecting decreased dopaminergic activity and homeostatic receptor upregulation [ 20 22 ], while others report no differences [ 23 25 ]. In contrast, PET and postmortem studies of adult MDD [ 26 , 27 ] and PET studies in geriatric LLD [ 28 ] consistently demonstrate lower dopamine transporter (DAT) availability in the putamen, NAc, ventral tegmental area, and superior midbrain. This reduction in DAT availability has been interpreted as possible compensatory downregulation due to low dopamine signaling.…”
Section: Dopaminergic System Changes Seen In Depression and The Effec...mentioning
confidence: 99%
“…Studies of D2/D3 receptor binding using PET in young or midlife populations are mixed, with some finding increased receptor availability in MDD, potentially reflecting decreased dopaminergic activity and homeostatic receptor upregulation [ 20 22 ], while others report no differences [ 23 25 ]. In contrast, PET and postmortem studies of adult MDD [ 26 , 27 ] and PET studies in geriatric LLD [ 28 ] consistently demonstrate lower dopamine transporter (DAT) availability in the putamen, NAc, ventral tegmental area, and superior midbrain. This reduction in DAT availability has been interpreted as possible compensatory downregulation due to low dopamine signaling.…”
Section: Dopaminergic System Changes Seen In Depression and The Effec...mentioning
confidence: 99%
“…SLC6A3 (a dopamine transporter gene) affects the function of the dopamine nerve system. In geriatric patients with severe major depressive disorder, a low level of dopamine transporter binding was found in the region of the nucleus accumbens and putamen ( Moriya et al, 2020 ). Alteration of dopamine transporter density in depressed patients with anhedonia showed reduced dopamine concentration in the synaptic cleft ( Sarchiapone et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides aripiprazole, it is also possible to hypothesize that the typical antagonism action on 5-HT2A of CAR might be usefu,l even in other antipsychotic-induced akathisia, as seen for mirtazapine, a 5-HT2A antagonist drug. 10 In the present case, we did not consider an ARI-LAI dose reduction based on the current clinical response, the previous failed treatments, and the fact the 300 mg might often not be suitable for severe patients. In conclusion, CAR is safe and useful, but further studies are required.…”
mentioning
confidence: 93%
“…A recent study using [ 18 F] FE-PE2I for positron emission tomography, which has high affinity and selectivity for DAT, revealed that geriatric patients with severe MDD showed significantly lower DAT binding in the nucleus accumbens than the controls. 10 However, it remains unclear whether the finding represents functional consequence or early dopaminergic neurodegeneration. Assessment of regional DAT availability in the striatum might provide data allowing the identification of a specific pattern of dopaminergic alteration possibly related to prodromal DLB.…”
mentioning
confidence: 99%